Cities and citizenship - Holston, James (Public culture books., 1999)
Cities and Citizenship is a prize-winning collection of essays that considers the importance of cities in the making of modern citizens. For most of the modern era the nation and not the city has been the principal domain of citizenship. This volume demonstrates, however, that cities are especially salient sites for examining the current renegotiations of citizenship, democracy, and national belonging. Just as relations between nations are changing in the current phase of global capitalism, so too are relations between nations and cities. Written by internationally prominent scholars, the essays in Cities and Citizenship propose that 'place' remains fundamental to these changes and that cities are crucial places for the development of new alignments of local and global identity. Through case studies from Africa, Europe, Latin America, and North America, the volume shows how cities make manifest national and transnational realignments of citizenship and how they generate new possibilities for democratic politics that transform people as citizens. Previously published as a special issue of Public Culture that won the 1996 Best Single Issue of a Journal Award from the Professional/Scholarly Publishing Division of the Association of American Publishers, the collection showcases a photo essay by Cristiano Mascaro, as well as two new essays by James Holston and Thomas Bender.